Emerging Challenges of Radiation-Associated Cardiovascular Dysfunction (RACVD) in Modern Radiation Oncology: Clinical Practice, Bench Investigation, and Multidisciplinary Care - Lee, Moon-Sing; Liu, Dai-Wei; Hung, Shih-Kai; Yu, Chih-Chia; Chi, Chen-Lin; Chiou, Wen-Yen; Chen, Liang-Cheng; Lin, Ru-Inn; Huang, Li-Wen; Chew, Chia-Hui; Hsu, Feng-Chun; Chan, Michael W. Y.; et al. (Frontiers in Cardiovascular Medicine, 2020)
Radiotherapy (RT) is a crucial treatment modality in managing cancer patients. However, irradiation dose sprinkling to tumor-adjacent normal tissues is unavoidable, generating treatment toxicities, such as radiation-associated cardiovascular dysfunction (RACVD), particularly for those patients with combined therapies or pre-existing adverse features/comorbidities. Radiation oncologists implement several efforts to decrease heart dose for reducing the risk of RACVD. Even applying the deep-inspiration breath-hold (DIBH) technique, the risk of RACVD is though reduced but still substantial. Besides, available clinical methods are limited for early detecting and managing RACVD. The present study reviewed emerging challenges of RACVD in modern radiation oncology, in terms of clinical practice, bench investigation, and multidisciplinary care. Several molecules are potential for serving as biomarkers and therapeutic targets. Of these, miRNAs, endogenous small non-coding RNAs that function in regulating gene expression, are of particular interest because low-dose irradiation, i.e., 200 mGy (one-tenth of conventional RT daily dose) induces early changes of pro-RACVD miRNA expression. Moreover, several miRNAs, e.g., miR-15b and miR21, involve in the development of RACVD, further demonstrating the potential bio-application in RACVD. Remarkably, many RACVDs are late RT sequelae, characterizing highly irreversible and progressively worse. Thus, multidisciplinary care from oncologists and cardiologists is crucial. Combined managements with commodities control (such as hypertension, hypercholesterolemia, and diabetes), smoking cessation, and close monitoring are recommended. Some agents show abilities for preventing and managing RACVD, such as statins and angiotensin-converting enzyme inhibitors (ACEIs); however, their real roles should be confirmed by further prospective trials.